Efektivitas Pemberian Jaminan Sosial kepada Pegawai - Waruwu, Wita Yarni; Meiman Hidayat Waruwu; Zega, Yamolala; Hulu, Fatolosa (Jurnal EMT KITA, 2024)
Social security plays an essential role in human resource (HR) management, particularly in improving employee welfare, as employees are key assets in any organization. This study aims to analyze the effectiveness of implementing the social security program at PT. Bank Sumut KCP Lahewa, North Nias Regency, and its impact on employees. A qualitative method was used, with interviews conducted to gain employees' views on the program's benefits. The results show that the program has been implemented effectively. Employees feel their well-being is supported through two health insurance options, Mandiri Inhealth and BPJS, which offer sufficient protection. This program enhances employees' sense of security and comfort, positively influencing their motivation and productivity. However, there are technical issues in the claims process that require further assessment. The study recommends that the company improve social security outreach, streamline the claims process, and consider additional relevant coverage options. Thus, social security is expected to further support employee welfare and foster a more productive work environment.
Keywords: Effectiveness; Social Security; Qualitative; Employees; PT. Bank Sumut